Visual body condition score of cows - Clarke, C.K.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Condition scores are often used to describe the "fleshiness" of cows. These scores range from 1 (extremely emaciated) to 9 (extremely fat).
Keywords: Beef; Visual body condition score; Beef cows